The STMIK Palangkaraya Student Satisfaction Index Application Based on National Standards of Higher Education in the Framework of Educational Quality Assurance: STMIK Palangkaraya Student Satisfaction Index Application Based - Ichsan, Mochammad (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2019)
Since 2003 the Directorate General of Higher Education has published the Higher Education Quality Assurance Manual. The book was then supplemented with Best Practices books which included Learning, Curriculum of Study Program, Human Resources, Student Affairs, Infrastructure and Facilities, Academic Atmosphere, Financial Management, Research and Publication, Community Service, and Governance. STMIK Palangkaraya continues to do this in improving higher education quality assurance by improving campus services and facilities and improving the quality of graduates. According to the national standards of higher education based on the regulation of the Minister of Research, Technology and Higher Education (Permenristekdikti) Number 44 of 2015, regarding the national standards of higher education. In this regulation the national standards of higher education cover national education standards, national research standards and national standards of community service. To facilitate STMIK in developing national education standards, the authors took the initiative to help STMIK to improve the standard by making a study entitled "STMIK Palangkaraya Student Satisfaction Index Application Based on National Standards of Higher Education in the Framework of Educational Quality Assurance". This application will make it easier to analyze and describe in detail and in depth about the level of student satisfaction with the STMIK Palangkaraya campus service so that it can meet the national education standards that have been set. Applications made using 8 (eight) database tables with the name imk_stmik.sql with software development methods namely the waterfall model.